Late vitreomacular traction in toxoplasma retinochoroiditis resolved by vitrectomy - Scarpa G (Dove Medical Press, 2013)
Giuseppe Scarpa, Stefano Fabris, Marco Di Gregorio, Francesca Urban Ophthalmic Department Regional Hospital, Ca' Foncello Piazza Ospedale 1, Treviso, Italy Abstract: This paper reports a case of late vitreomacular traction in a young patient secondary to toxoplasma retinochoroiditis resolved by vitrectomy. A 17-year-old female with chronic inflammatory bowel disease developed severe vitreomacular traction 8 months after resolution of ocular toxoplasmosis with medical therapy. Best-corrected visual acuity, full ophthalmic slit-lamp examination, colour fundus photography, spectral domain optical coherence tomography, and fluorescein angiography were performed. The patient underwent vitrectomy with removal of the clinically evident posterior hyaloid. Vitrectomy was rapidly successful in resolving the vitreomacular traction, with full recovery in best-corrected visual acuity of 20/20. Vitreoretinal traction in patients with previous toxoplasma retinochoroiditis may appear several months after resolution of the inflammatory condition. We suggest observing carefully for possible development of late vitreoretinal traction during follow-up of such patients. Keywords: ocular toxoplasmosis, toxoplasma retinochoroiditis, vitreomacular traction, vitrectomy, inflammatory bowel disease